Ecological and Socio-Economic Factors on the Rate of Participation and Sustainable Forest Management - Marnelly, T. Romi; Dahril, Tengku; Saam, Zulfan; Nofrizal, Nofrizal (International Journal of Energy Economics and Policy, 2023)
This research was conducted to examine the effect of ecological, social and economic factors on the rate of partcipation of local communities on sustainable forest management. This research also want to examine the effect of ecological, social and economi factors on the forest sustainability and exploring the mediating role of rate of partcipation of local communities to increase the sustainability level of forest management. In this study, social forestry is examined from a comprehensive viewpoint that includes economic, societal, and ecological factors in order to illustrate the factors that influence local community participation in sustainable forest management in Riau, Indonesia. The use of Partial Least Square- Structural Equation Modeling (PLS-SEM) with SmartPLS software has revealed that both ecological and socio-economic factors determine the level of local community participation in sustainable forest management. The results have the potential to serve as a point of reference in the advancement of environmental science and environmental sociology, along with providing theoretical understanding about customary forests and local communities. Additionally, the practical implications of the findings can guide the sustainable development of forest resources. Ultimately, these findings are expected to yield optimal solutions for local communities in their efforts to manage customary forests sustainably.